Anthracyclines suppress pheochromocytoma cell characteristics, including metastasis, through inhibition of the hypoxia signaling pathway - Pang, Ying; Yang, Chunzhang; Schovanek, Jan; Wang, Herui; Bullova, Petra; Caisova, Veronika; Gupta, Garima; Wolf, Katherine I; Semenza, Gregg L; Zhuang, Zhengping; Pacak, Karel (Oncotarget, 2017)
Pheochromocytomas (PHEOs) and paragangliomas (PGLs) are rare, neuroendocrine tumors derived from adrenal or extra-adrenal chromaffin cells, respectively. Metastases are discovered in 3-36% of patients at the time of diagnosis. Currently, only suboptimal treatment options exist. Therefore, new therapeutic compounds targeting metastatic PHEOs/PGLs are urgently needed. Here, we investigated if anthracyclines were able to suppress the progression of metastatic PHEO. We explored their effects on experimental mouse PHEO tumor cells using in vitro and in vivo models, and demonstrated that anthracyclines, particularly idarubicin (IDA), suppressed hypoxia signaling by preventing the binding of hypoxia-inducible factor 1 and 2 (HIF-1 and HIF-2) to the hypoxia response element (HRE) sites on DNA. This resulted in reduced transcriptional activation of HIF target genes, including erythropoietin (EPO), phosphoglycerate kinase 1 (PGK1), endothelin 1 (EDN1), glucose transporter 1 (GLUT1), lactate dehydrogenase A (LDHA), and vascular endothelial growth factor (VEGFA), which consequently inhibited the growth of metastatic PHEO. Additionally, IDA downregulated hypoxia signaling by interfering with the transcriptional activation of HIF1A and HIF2A. Furthermore, our animal model demonstrated the dose-dependent suppressive effect of IDA on metastatic PHEO growth in vivo. Our results indicate that anthracyclines are prospective candidates for inclusion in metastatic PHEO/PGL therapy, especially in patients with gene mutations involved in the hypoxia signaling pathway.
Keywords: Endothelin-1; signální transdukce; Idarubicin; Signal Transduction; paraganglioma; myši nahé; fosfoglycerátkinasa; Humans; erythropoetin; Adrenal Gland Neoplasms; Pheochromocytoma; Protein Binding; pheochromocytoma; anthracyclines; Antineoplastic Agents; endotelin-1; Hypoxia; Mice, Nude; lidé; Erythropoietin; Phosphoglycerate Kinase; zvířata; metastatic; myši; Hypoxia-Inducible Factor 1, alpha Subunit; Mice; buňky - růstové procesy; hypoxie; idarubicin; faktor 1 indukovatelný hypoxií - podjednotka alfa; xenogenní modely - testy protinádorové aktivity; Neoplasm Metastasis; hypoxia-inducible factors; metastázy nádorů; vazba proteinů; nádorové buněčné linie; protinádorové látky; transkripční faktory bHLH; nádory nadledvin; Xenograft Model Antitumor Assays; Animals; Cell Line, Tumor; Cell Growth Processes; feochromocytom; Basic Helix-Loop-Helix Transcription Factors